2005
DOI: 10.1099/ijs.0.63333-0
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum subsp. argentoratensis subsp. nov., isolated from vegetable matrices

Abstract: Lactobacillus plantarum belongs to the Lactobacillus caseiPediococcus phylogenetic group of the genus Lactobacillus (Hammes & Vogel, 1995) and in particular to the L. plantarum phylogenetic subgroup (Hammes & Hertel, 2003). This species is characterized by many metabolic activities that allow it to colonize different environments such as dairy products, pickled vegetables, fish products, silage, wine as well as mammal intestinal tracts (Vescovo et al., 1993). The species is highly heterogeneous (Dellaglio et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 16 publications
3
71
0
2
Order By: Relevance
“…Lactobacillus plantarum group include L. plantarum, L. pentosus and L. paraplantarum. These three closely related species have very similar fermentation abilities and cannot be distinguished by 16S rRNA gene sequence analysis because they show 99 % sequence similarity [26]. In view of its demonstrated effectiveness, sequence analysis of protein coding genes as alternative phylogenetic markers was applied to difference L. plantarum group.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum group include L. plantarum, L. pentosus and L. paraplantarum. These three closely related species have very similar fermentation abilities and cannot be distinguished by 16S rRNA gene sequence analysis because they show 99 % sequence similarity [26]. In view of its demonstrated effectiveness, sequence analysis of protein coding genes as alternative phylogenetic markers was applied to difference L. plantarum group.…”
Section: Discussionmentioning
confidence: 99%
“…2) [15]. Hence 16S rDNA analysis by sequencing or restriction fragment length polymorphism (RFLP) of the LAB strains can at the most indicate, only a belonging to the L. plantarum group, but not to a defi nite species.…”
Section: Resultsmentioning
confidence: 99%
“…As a slowly diverging molecule, 16S rRNA is not able to reveal signifi cant differences among recently diverged species such as L. plantarum, L. paraplantarum and L. pentosus, or L. casei, L. rhamnosus and L. zeae [16]. To obtain a more detailed identifi cation, at species level, analysis of recA gene was undertaken, which has been described as a phylogenetic marker capable of differentiating the closely related members of the L. plantarum group [14,15,17]. The nested multiplex assay exploiting the variable nucleotide regions of recA gene proposed by Torriani et al [14] revealed that 13 LAB strains which exhibited the 107 bp amplicon were of L. paraplantarum species whereas the remaining three LAB strains which showed 218 bp amplicon belonged to L. pentosus species.…”
Section: Resultsmentioning
confidence: 99%
“…To fingerprint isolated strains, multiplex-PCR, rep-PCR and RAPD-PCR-analysis were obtained as useful methods (Bringel et al 2005, Mäkimattila et al 2011, Parente et al 2010) so as Torriani et al (2001a) used combination of RAPD-PCR patterns with ALFP effectively in differentiation strains of Lb. plantarum-group.…”
Section: Introductionmentioning
confidence: 99%